Investigar La Problemática Que Ha Causado El Bachillerato General Unificado En La Formación Académica De Los Estudiantes Del Primer Año De Bachillerato Del Colegio Nacional “Gonzalo Albán Rumazo”, Parroquia Aláquez, Cantónlatacunga, Año Lectivo 2012 - 2013 - Catota Chicaiza, Nancy Germania (2013)
The present research has as main objective to develop training workshops regarding the implementation of the new General Unified School aimed at students, teachers and parents, it is not beneficial in the academic training of students as difficulties exist for entry to universities and in turn do not have adequate information on this new educational model, it was applied to instruments that collect information relevant to the topic, in which disagreement was evident in authorities, teachers and students about the General applicability of the Unified New School, this research is considered significant because it allows the students to have enough knowledge about what has caused the inappropriate application of the New Unified General Baccalaureate (BGU) investigated the contents contain updated information effectively guide the development of the proposed theme and can serve as a source of advice to anyone interested in the subject.